Perfectly blind image watermarking scheme with multi-purpose based on region segment for sub-block and self-embedding technology - Tian-yu YE (Tongxin xuebao)
A perfectly blind image watermarking scheme with multi-purpose was proposed through region segment for sub-block and self-embedding technology, which could achieve copyright identification and content authentication only with the help of an attacked image. The original image was split into non-overlapping blocks, and each block was con-ducted with discreet cosine transformation. Each block's discreet cosine transformation matrix was divided into region 1 and region 2. Then, after the region 1 was conducted with singular value decomposition,a feature watermark was derived from judging the parity of the first digit from average of singular values. Moreover, the feature watermark was self-embedded into region 2 by adjusting two discreet cosine transformation alternative current coefficients. Finally, a watermarked image was obtained after conducting inverse discrete cosine transformation on each block. The proposed algorithm achieved perfectly blind detection and multi-purpose by combining self-embedding feature watermark from re-gion 1 into region 2 and blindly extracting authentication watermark n region 2. Experimental results show that the pro-posed algorithm can achieve both copyright protection and content authentication, and has the ability to distinguish mali-cious tamper and unintentional tamper.